The Role of Agenpos B2B Marketing Strategy in Enhancing the Competitive Advantage of PT Pos Indonesia Boyolali Branch - Putri, Tasya Wianda; Ridanasti, Erlita (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to implement the Agenpos B2B marketing strategy implemented by PT Pos Indonesia Boyolali to develop and enhance the company's competitiveness amidst increasingly fierce competition in the logistics industry. The method used was a descriptive qualitative approach through direct observation and interviews with marketing division employees. The results indicate that the implemented marketing strategy still faces various challenges, particularly the difficulty of finding new Agenpos B2B customers and increasing consumer expectations. PT Pos Indonesia Boyolali Branch has implemented an integrated marketing approach through market segmentation and targeting, but still needs optimization, particularly in terms of promotion and customer service. This evaluation recommends improving digital capabilities, utilizing information technology, and strengthening partnerships to retain customers and expand market share. With the right strategy, Agenpos B2B has great potential to become a competitive and superior distribution channel in the digital era.